Two-dimensional and contrast-enhanced ultrasound of intestinal ischaemia in cats: four cases. Issue 4 (April 2020) - Linta, Nikolina; Baron Toaldo, Marco; Del Magno, Sara; Pey, Pascaline; Quinci, Manuela; Diana, Alessia
Objectives: The aim of this study was to describe the results of two-dimensional (2D) and contrast-enhancement ultrasound (CEUS) in four cats with intestinal ischaemia. Methods: Data were collected from hospital records of all cats that had intestinal ischaemia between January 2012 and August 2018. The inclusion criteria were complete abdominal ultrasound examination, colour flow Doppler and CEUS of lesions, confirmation of intestinal ischaemia detected by visual assessment of avascular intestinal segment at surgery, and/or necropsy and histopathology. All images and video clips were reviewed by the same experienced operator. Results: Four cats with different intestinal ischaemic lesions were included in the study: duodenal perforating ulcer, jejunal necrotising enteritis, necrosis secondary to jejunojejunal intussusception and iatrogenic damage of jejunal arteries. On the 2D ultrasound, all intestinal lesions were characterised by non-specific findings: focal hypoechoic wall thickening with loss of normal layering associated with hyperechoic mesentery surrounding the intestinal tract. CEUS showed a reduced or absent enhancement of the intestinal lesions in comparison to the surrounding perfused wall. Conclusions and relevance: Intestinal ischaemia is a potentially fatal disorder. Grey-scale, colour and power Doppler ultrasonography are not sensitive for evaluating this condition. Our preliminary findings illustrate the usefulness of CEUS for the detection of intestinal wall impaired perfusion in cats.